Dampak dan Tantangan Pemanfaatan ChatGPT bagi Pembelajaran Pendidikan Agama Islam - Luthfiatul Udhma; Hamam Burhanuddin (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The rapid advancement of generative artificial intelligence, particularly ChatGPT, has significantly influenced educational practices, including the teaching and learning of Islamic education. ChatGPT offers considerable opportunities by providing diverse instructional materials, expediting the preparation of teaching documents, and supporting personalized learning based on students’ abilities and learning preferences. Additionally, it functions as a supplementary learning resource capable of facilitating religious discussions, explaining abstract concepts, and fostering critical thinking skills through fast and adaptive feedback. Nevertheless, the use of ChatGPT in Islamic education also presents noteworthy challenges. The risks of misinformation and hallucination may affect students’ understanding, especially in religious matters that require high accuracy and reliable references. Other challenges include academic integrity concerns, excessive reliance on technology, content bias, and the model’s limited ability to interpret Islamic socio-religious contexts in Indonesia. Furthermore, disparities in digital literacy among teachers and students hinder optimal implementation. This article aims to provide a comprehensive analysis of these impacts and challenges by examining recent literature and empirical studies. The findings indicate that ChatGPT can offer substantial benefits for Islamic education learning when integrated critically and responsibly, supported by enhanced teacher competencies, clear institutional AI policies, and strong emphasis on ethics and source verification. Thus, ChatGPT holds the potential to serve as a strategic innovation for improving the quality of Islamic Religious Education in the digital era.